Pengaruh Administrasi Perpajakan, Kualitas Layanan Fiskus, Terhadap Perilaku Wajib Pajak Dan Kepatuhan Wajib Pajak (Studi Pada Wajib Pajak Badan Di Kantor Pelayanan Pajak Kota Malang Selatan 2015) - Muhammad Yusril; M Awaluddin (Universitas Muhammadiyah Mataram, 2018)
The research was motivated by the demands of the increasing government revenues, especially in the sector of taxation, both form all repair and fundamental change in all aspects of taxation. One of them is the demans on taxpayer compliance. Taxpayer compliance in implementing the tax obligations can not be separated from the role of the tax administration system that has been determined by the government and also the attitude of the public taxpayer itself. In addition, one of the efforts that are not less important is the government’s efforts in improving taxpayer satisfaction through improved quality of service performed by the tax authorities which is expected to have an impact on taxpayer compliance. This study aims to determine the effect of the tax administration and the quality of service performed by tax authorities to taxpayer compliance is mediated by the behavior of taxpayer. This research is explanatory reseach using a quantitative approach. This data using primary data sources are derived from filling the questionnaire and interviews whit taxpayer that registered in tax office south Malang and assisted with a variety of relevant secondary data. Data were collected using accidental sampling method and analyzed by using path analysis in SPSS version 20. The results showed that both the tax administration, the quality of service performed by the tax authorities, and the behavior of taxpayer directly have a significant impact on taxpayer compliance. The results also show that the tax administration and the the quality of service performed by the tax authorities has a significant effect when mediated through the behavior of taxpayer. Therefore, based on the reseach that has been done, then all hypotheses that have been constructed in this study is acceptable. Various limitations faced by researchers is expected to become a challenge for future research to obtain reseach results further illustrate the factor that influence the increase taxpayer compliance.